2022
DOI: 10.1590/2177-6709.27.5.e222115.oar
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of palatal dimensions in different facial patterns by using digital dental casts

Abstract: Objective: To analyze the variations of hard palate volume in adults with normal occlusion and different facial types and patterns, by using a three-dimensional analysis on digital casts. Methods: The dental casts of 70 Caucasian adults (28 men, 42 women), mean age of 16.4 years (SD 1.3 years), were scanned by using a tridimensional scanner (Delcam PowerSHAPE™, 2010, Birmingham, UK). Close points were selected in the gingival and cervical regions on the lingual surface of the maxillary teeth, to analyze palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…No differences in the facial width between the two groups is in accordance with the findings of a recent study by Kairalla et al, 2022, wherein no significant correlations were reported between the different facial forms and the width, height, length, and volume measurements of the palate in a Brazilian Caucasian population [ 29 ]. Furthermore, it has previously been reported that dental arches are poor predictors of transverse skeletal dimensions [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…No differences in the facial width between the two groups is in accordance with the findings of a recent study by Kairalla et al, 2022, wherein no significant correlations were reported between the different facial forms and the width, height, length, and volume measurements of the palate in a Brazilian Caucasian population [ 29 ]. Furthermore, it has previously been reported that dental arches are poor predictors of transverse skeletal dimensions [ 25 ].…”
Section: Discussionsupporting
confidence: 91%